Prolonged Length of Stay in the Emergency Department and Mortality in Critically Ill Elderly Patients with Infections: A Retrospective Multicenter Study. (19th July 2021) - Choi, Wonjin; Woo, Seon Hee; Kim, Dae Hee; Lee, June Young; Lee, Woon Jeong; Jeong, Sikyoung; Cha, Kyungman; Youn, Chun Song; Park, Sanghyun
Abstract : Background . This study aimed at investigating whether the length of stay (LOS) in the emergency department (ED) is associated with mortality in elderly patients with infections admitted to the intensive care unit (ICU). Delayed admission to the ICU may be associated with adverse clinical outcomes in elderly patients with infections. Methods . This was a retrospective study conducted with subjects over 65 years of age admitted to the ICU from 5 EDs. We recorded demographic data, clinical findings, initial laboratory results, and ED LOS. Outcomes were all-cause in-hospital mortality and hospital LOS. A multivariable regression model was applied to identify factors predictive of mortality. Results . A total of 439 patients admitted to the ICU via the ED were included in this study, 132 (30.1%) of whom died in the hospital. The median (IQR) age was 78 (73, 83) years. In multivariable analysis, a history of malignancy (OR: 3.76; 95% CI: 1.88–7.52; p < 0.001 ), high lactate level (OR: 1.13; 95% CI: 1.01–1.27; p = 0.039 ), and ED LOS (OR: 1.01; 95% CI: 1.00–1.02; p = 0.039 ) were independent risk factors for all-cause in-hospital admission. Elderly patients with an ED LOS >12 hours had a longer hospital LOS (p = 0.018 ), and those with an ED LOS > 24 hours had a longer hospital LOS and higher mortality rate (p = 0.044,   p = 0.008 ). Conclusions . This study shows that prolonged ED LOS is independently associated with all-cause in-hospital mortality in elderly patients with infections requiring ICU admission. ED LOS should be considered in strategies to prevent adverse outcomes in elderly patients with infections who visit the ED.